Soybean Embryonic Axis Transformation: Combining Biolistic and Agrobacterium-Mediated Protocols to Overcome Typical Complications of In Vitro Plant Regeneration - Paes de Melo, Bruno; Lourenço-Tessutti, Isabela Tristan; Morgante, Carolina Vianna; Santos, Naiara Cordeiro; Pinheiro, Luanna Bezerra; de Jesus Lins, Camila Barrozo; Silva, Maria Cristina Matar; Macedo, Leonardo Lima Pepino; Fontes, Elizabeth Pacheco Batista; Grossi-de-Sa, Maria Fatima (Frontiers in Plant Science, 2020)
The first successful attempt to generate genetically modified plants expressing a transgene was preformed via T-DNA-based gene transfer employing Agrobacterium tumefaciens-mediated genetic transformation. Limitations over infectivity and in vitro tissue culture led to the development of other DNA delivery systems, such as the biolistic method. Herein, we developed a new one-step protocol for transgenic soybean recovery by combining the two different transformation methods. This protocol comprises the following steps: agrobacterial preparation, seed sterilization, soybean embryo excision, shoot-cell injury by tungsten-microparticle bombardment, A. tumefaciens-mediated transformation, embryo co-cultivation in vitro, and selection of transgenic plants. This protocol can be completed in approximately 30 - 40 weeks. The average efficiency of producing transgenic soybean germlines using this protocol was 9.84%, similar to other previously described protocols. However, we introduced a more cost-effective, more straightforward and shorter methodology for transgenic plant recovery, which allows co-cultivation and plant regeneration in a single step, decreasing the chances of contamination and making the manipulation easier. Finally, as a hallmark, our protocol does not generate plant chimeras, in contrast to traditional plant regeneration protocols applied in other Agrobacterium-mediated transformation methods. Therefore, this new approach of plant transformation is applicable for studies of gene function and the production of transgenic cultivars carrying different traits for precision-breeding programs.